Intestinal perforation during chemotherapeutic treatment of intra-abdominal desmoid tumor in patients with Gardner’s syndrome: report of two cases - Li, Wei (World J Surg Oncol, 2016)
BACKGROUND: A minority of intra-abdominal desmoid tumors is associated with Gardner’s syndrome in which desmoid tumors become an important cause of morbidity and mortality if they are surgically unresectable. CASE PRESENTATION: Here, we report two cases of intestinal perforation during chemotherapy in patients with Gardner’s syndrome-associated intra-abdominal desmoids. One female and one male patients who developed inoperable desmoids were given the chemotherapeutic regimen of doxorubicin plus dacarbazine, followed by meloxicam. Significant tumor regression was observed clinically. However, intestinal perforation happened in both patients. They were subjected to emergency surgery, follow-up management, and survived up to now. CONCLUSIONS: The doxorubicin plus dacarbazine chemotherapy is an effective treatment for intra-abdominal demoid tumors in patients with Gardner’s syndrome. On the other hand, given severe adverse events might occur, clinicians should pay more attention that tumor quick regression may cause intestinal perforation in which urgent surgical intervention is necessary.